2017
DOI: 10.1681/asn.2016101121
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Steroid-Resistant Nephrotic Syndrome in Children

Abstract: We investigated the value of genetic, histopathologic, and early treatment response information in prognosing long-term renal outcome in children with primary steroid-resistant nephrotic syndrome. From the PodoNet Registry, we obtained longitudinal clinical information for 1354 patients (disease onset at >3 months and <20 years of age): 612 had documented responsiveness to intensified immunosuppression (IIS), 1155 had kidney biopsy results, and 212 had an established genetic diagnosis. We assessed risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
192
1
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 167 publications
(214 citation statements)
references
References 39 publications
10
192
1
11
Order By: Relevance
“…Detection of a hereditary podocytopathy is a prognostic indicator of favorable and poor long-term outcomes [4]. Genetic SRNS is associated with a high rate of ESRD in 66% of patients.…”
Section: Prognosis In Genetic Srnsmentioning
confidence: 99%
See 4 more Smart Citations
“…Detection of a hereditary podocytopathy is a prognostic indicator of favorable and poor long-term outcomes [4]. Genetic SRNS is associated with a high rate of ESRD in 66% of patients.…”
Section: Prognosis In Genetic Srnsmentioning
confidence: 99%
“…Patients with non-genetic disease developed ESRD less frequently than patients with genetic disease (27 versus 74%). Trautmann et al showed that 10-and 15-year ESRD-free survival rates in patients with a genetic diagnosis (27 and 17%) were much lower than those in patients without a genetic diagnosis (53 and 48%) [4]. Further breakdown by genetic diagnosis showed largely uniform renal survival times of the major genetic entities, with estimated 10-year ESRD-free survival rates of 28% for NPHS2-associated nephropathy, 23% for WT1-associated disease, and 29% for the less common podocytopathies [4].…”
Section: Prognosis In Genetic Srnsmentioning
confidence: 99%
See 3 more Smart Citations